PENGEMBANGAN SISTEM INFORMASI PENJADWALAN JURUSAN TEKNIK INFORMATIKA UNIKOM - Dewi Mustari (LPPM, 2011)
The exiting schedule application system which is used in informatics Engineering Department at Universitas Komputer Indonesia has not meet it’s usability and clear function based on the main purpose to manage the schedule time for lecturing activity. In this regard some problems emerge and need some attentions to be solved as good as possible. The main concern is how to develop a better application scheduling system. The previous application in used does not have a well documented development blue print, nothing but the program execution only. Later, it makes the further development become difficult. Based on the fact mentioned above the main purpose to achieved is to make a well documented development blue print along with the implementation of making a better lecture schedule application system, and the final goal to support the lecturing management becomes handy in practice is possible to attain. Keyword: Schedule, development, application